Evaluation of Alere i RSV for rapid detection of respiratory syncytial virus in children hospitalized with acute respiratory tract infection - Peters, Rebecca; Schnee, Sarah Valerie; Tabatabai, Julia; Schnitzler, Paul; Pfeil, Johannes (Journal of clinical microbiology, 2017)
Alere™ i RSV is a novel rapid test which applies a nicking enzyme amplification reaction to detect respiratory syncytial virus in point-of-care settings. In this study, we evaluated the Alere™ i RSV assay by using frozen nasopharyngeal swab samples that were collected in viral transport medium from children hospitalized with acute respiratory tract infection during winter season 2015/2016. Alere™ i RSV assay test results were compared to Altona® RealStar RSV real-time reverse transcription PCR (RT-PCR). We found that the overall sensitivity and specificity of the Alere™ i RSV test assay was 100% (CI95 93% - 100%) and 97% (CI95 89% - 100%), respectively. Positive samples were identified within 5-7 minutes from sample collection. Overall, the Alere™ i RSV test assay performed well in comparison to the RT-PCR assay and has the potential to facilitate the detection of RSV in point-of-care settings.